2017
DOI: 10.1007/s10827-017-0647-7
|View full text |Cite
|
Sign up to set email alerts
|

The influence of depolarization block on seizure-like activity in networks of excitatory and inhibitory neurons

Abstract: The inhibitory restraint necessary to suppress aberrant activity can fail when inhibitory neurons cease to generate action potentials as they enter depolarization block. We investigate possible bifurcation structures that arise at the onset of seizure-like activity resulting from depolarization block in inhibitory neurons. Networks of conductance-based excitatory and inhibitory neurons are simulated to characterize different types of transitions to the seizure state, and a mean field model is developed to veri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 48 publications
4
30
0
Order By: Relevance
“…The earliest preictal change we observed was a loss of the strong spike-field coherence of PV cell spiking to a prominent low-gamma band previously observed in mouse hippocampus ( Chen et al, 2011 ; Cabral et al, 2014 ; Sauer et al, 2015 ). Previous work has suggested that increased inhibitory synaptic activity or the onset of depolarization block in fast-spiking interneurons could precipitate seizure onset ( Velazquez and Carlen, 1999 ; Timofeev et al, 2002 ; Ziburkus et al, 2006 ; Fujiwara-Tsukamoto et al, 2007 ; Gnatkovsky et al, 2008 ; Cammarota et al, 2013 ; Kim and Nykamp, 2017 ), and we found that the onset of ictal spikes occurred immediately after a sharp increase in PV interneuron spiking in both anesthetized and awake animals. However, we found no evidence for decreased interneuron spike amplitude prior to ictal onset, suggesting that these interneurons did not enter depolarization block prior to ictal onset.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The earliest preictal change we observed was a loss of the strong spike-field coherence of PV cell spiking to a prominent low-gamma band previously observed in mouse hippocampus ( Chen et al, 2011 ; Cabral et al, 2014 ; Sauer et al, 2015 ). Previous work has suggested that increased inhibitory synaptic activity or the onset of depolarization block in fast-spiking interneurons could precipitate seizure onset ( Velazquez and Carlen, 1999 ; Timofeev et al, 2002 ; Ziburkus et al, 2006 ; Fujiwara-Tsukamoto et al, 2007 ; Gnatkovsky et al, 2008 ; Cammarota et al, 2013 ; Kim and Nykamp, 2017 ), and we found that the onset of ictal spikes occurred immediately after a sharp increase in PV interneuron spiking in both anesthetized and awake animals. However, we found no evidence for decreased interneuron spike amplitude prior to ictal onset, suggesting that these interneurons did not enter depolarization block prior to ictal onset.…”
Section: Discussionsupporting
confidence: 59%
“…Previous work has also highlighted the potential preictal contribution of excitatory GABAergic effects due to Cl- accumulation ( Cossart et al, 2005 ; Palma et al, 2006 ; Miles et al, 2012 ) or loss of inhibition due to depletion of GABAergic release ( Zhang et al, 2012 ). Interneuron firing may also transiently cease during ictal events as a result of depolarization block ( Ziburkus et al, 2006 ; Cammarota et al, 2013 ; Kim and Nykamp, 2017 ). Developmental dysregulation of inhibitory interneurons causes chronic epileptic disorders ( Lau et al, 2000 ; Cobos et al, 2005 ; Rossignol et al, 2013 ; Tai et al, 2014 ), and interneurons also appear to be particularly sensitive to seizure-related damage ( Sloviter, 1987 ; de Lanerolle et al, 1989 ; Robbins et al, 1991 ; Rice et al, 1996 ; Gibbs et al, 1997 ; Cossart et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…Notice that the ML model shows a decrease of firing rate at frequencies higher than 8 Hz (i.e. no voltage oscillations and thus no firing activity), as reported previously for this model by Kim and Nykamp (2017). This is a consequence of the depolarization block (DB) observed at high input frequencies (i.e.…”
Section: Transfer Function For Complex Modelssupporting
confidence: 79%
“…Thus such modeling is on the opposite extreme of detail in comparison to the proposed Epileptor-2 model. Another critical point to the fourth assumption is its validity in the case of the depolarization block, which occurs in interneurons during IDs [ 1 , 47 ]. Therefore, the approximation might overestimate the inhibitory currents as well as the potassium accumulation mediated by the accumulation of chloride and the activity of K-Cl-cotransporters during some period within an ID.…”
Section: Discussionmentioning
confidence: 99%